Per una nuova polis - Villani, Tiziana (Scienze del Territorio, 2015)
In 2030 the urban revolution will be accomplished on a global scale, since the most part of the world population will live in a city. That entails changes involving resources, land consumption, living conditions, institutions, as well as the economic and social models driving this change. The very notion of space seems obsolete in the face of this urbanization, which redefines living, re-lationships, and the same people involved at such a quick pace and requires to redefine the forms of the third millennium ‘polis’ in order to ‘meet’ new ways of living. Even if capitalism gave this pro-cess a mark of ultra-liberalism that outlines conflict areas increasingly large and painful, cities are still ‘lands of hope’, the scattered, self-built, chaotic and provisional settlements recount attempts to experience life places less excluding and devoid of hope. The ‘Nature’ we live in, thus, can be no more a joyful lost state, it will be the place where we must use all the ‘fantasy’ requested to find a way out of the insane dominant model. That is where knowledge must play a renewed critical and creative function, escaping the control of techno-bureaucratic elites that have actually abolished public space reserving it for consumption, marketing and the ‘brand’. We are this very nature, con-stantly changing, and we must take part in a conflict in which our very lives are at stake.